The Amentoflavone-Rich Extract of Ouratea fieldingiana Leaves Presents Antioxidant and Anti-inflammatory Activity in Mice - Lucas Soares Frota; Francisco Glerison da Silva Nascimento; Leonardo Soares Freitas; Francisco Flavio da Silva Lopes; Ramon Róseo Paula Pessoa Bezerra de Menezes; Alana de Freitas Pires; Rondinelle Ribeiro Castro; Ana Maria Sampaio Assreuy; Selene Maia de Morais (Archives of Current Research International, 2024)
Aims: To evaluate the antioxidant and anti-inflammatory effects of the Ouratea fieldingiana leaf extract (OFE) and its main constituent amentoflavone (AMT). Study Design: The phenolic compounds of Ouratea fieldingiana leaves (OFE) were quantified, the chemical structure characterized and the anti-inflammatory effect of OFE and amentoflavone was evaluated in mice paw edema and peritonitis. Place and Duration of Study: The work involved the partnership of the Natural Products Chemistry Laboratory and Inflammation Physio pharmacology Laboratory, between July 2020 and June 2021. Methodology: The OFE was obtained from 70% ethanol extract of O. fieldingiana. OFE was subjected to classic chromatographic column furnishing AMT. The phenolic compounds were characterized by HPLC and quantified by Follin-Ciocalteu methodology. The antiradical potential was evaluated by DPPH and ABTS methods. Anti-inflammatory activity was determined in female Swiss mice received per oral OFE (0.1-10 mg/kg) or sterile saline 60 min before stimulation with carrageenan (300 mg) for quantification of the parameters: edema, abdominal hypernociception, neutrophil migration and oxidative stress markers (reduced glutathione, malondialdehyde, myeloperoxidase and catalase activities). Results: AMT was identified as the main compound in the OFE (292.64 ± 3.87 mg/g extract). OFE has an average inhibitory concentration of 9.81 ± 0.17 µg/mL extract to inhibit the DPPH radical. OFE and AMT inhibited paw edema [OFE: 32% (0-2 h), 28% (2-4 h); AMT: 55% (0-2h); 51% (2-4 h)], neutrophil migration (OFE: 65%; AMT: 67%); myeloperoxidase activity (OFE: 37%; AMT: 45%) and abdominal hypernociception (OFE: 31%; AMT: 35%). OFE, but not AMT, increased catalase activity (57%) and reduced glutathione (62%), but decreased malondialdehyde (69%). Conclusion: The amentoflavone-rich extract from O. fieldingiana leaves presents antioxidant activity in vitro and in vivo, and anti-inflammatory activity in vivo, corroborating the popular use of the plant.